Insulin can regulate GLUT4 internalization by signaling to Rab5 and the motor protein dynein - Huang, Jie (The National Academy of Sciences, 2001)
Insulin stimulates glucose transport by promoting translocation of the insulin-sensitive glucose transporter isoform 4 (GLUT4) from an intracellular compartment to the cell surface. This movement is accomplished by stimulation of GLUT4 exocytosis as well as inhibition of endocytosis. However, the molecular mechanisms for these effects remain unclear. In this study, we found that the GTP-binding protein Rab5 physically associated with the motor protein dynein in immunoprecipitants from both untransfected cells and cells transfected with GFP-Rab5 constructs. Microinjection of anti-Rab5 or anti-dynein antibody into 3T3-L1 adipocytes increased the basal level of surface GLUT4, did not change the insulin-stimulated surface GLUT4 level, and inhibited GLUT4 internalization after the removal of insulin. Photoaffinity labeling of Rab5 with [γ-(32)P]GTP-azidoanilide showed that insulin inhibited Rab5-GTP loading. By using microtubule-capture assays, we found that insulin also caused a significant decrease in the binding of dynein to microtubules. Furthermore, pretreatment of cells with the PI3-kinase inhibitor LY294002 inhibited the effects of insulin on both Rab5-GTP loading and dynein binding to microtubules. In conclusion, these data indicate that insulin signaling inhibits Rab5 activity and the interaction of dynein with microtubules in a PI3-kinase-dependent manner, and that these effects may inhibit the rate of GLUT4 internalization. As such, our results present a previously uncharacterized insulin-signaling pathway involving Rab5, the motor protein dynein, and the cytoskeleton to regulate directional GLUT4 movement, facilitating GLUT4 distribution to the cell surface.